Culicimermis schakhovii gen. et. sp. n. (Mermithidac) — новый паразит комаров - Рубцов, И.А.; Исаева, Н.М. (Вестник зоологии, 1975)
Some nidi of mermitosis were found in six mosquito species of the genus Aedes in temporary water bodies from the Kiev environs. Culicimermis schakhovii- a new species of the new genus which is similar to the genus Perutilimermis Nickle, but essentially differs in two spicules (instead of one) and a short vagina (instead of long one). The development proceeds in larvae and pupae but is over at the adult stage of the mosquito. When infestation is weak (1-2 parasites in a host), mosquitoes are swarming, from time to time attacking somebody for blood-sucking. Mosquito infestation with the above-men- tioned species ranges in different years from 20 to 60% and higher.